Filamentous fungi from the Atlantic marine sponge Dragmacidon reticulatum - Passarini, Michel R. Z.; Santos, Cledir; Lima, Nelson; Berlinck, Roberto G. S.; Sette, Lara D. [UNESP] (Springer Nature, 2013)
Dragmacidon reticulatum is a marine sponge of wide occurrence in the Eastern and Western Atlantic. Little is known about D. reticulatum fungal diversity. Filamentous fungi recovered from D. reticulatum were assessed in the present study using a polyphasic taxonomic approach, including classical morphology, molecular biology and MALDI-TOF ICMS. Ninety-eight fungal strains were isolated from two D. reticulatum samples by using six different culture media, which were identified up to the genus level. Sixty-four distinct fungal ribotypes were obtained, distributed among twenty-four different genera belonging to the Ascomycota and Zygomycota. Representatives of Penicillium and Trichoderma were the most diverse and abundant fungi isolated. Amongst Penicillium spp. three isolates belonged to the same ribotype can be considered as a putative new species. Data derived from the present study highlight the importance of using a polyphasic approach to get an accurate identification in order to structure a reliable culture collection. © 2012 Springer-Verlag Berlin Heidelberg.
Keywords: Filamentous fungi; MALDI-TOF ICMS; Marine sponge; Polyphasic taxonomy; ribosome DNA; Annulohypoxylon; Ascomycetes; biodiversity; Bionectria; Biscogniauxia; controlled study; DNA sequence; Dragmacidon reticulatum; filamentous fungus; fungus; fungus identification; fungus isolation; marine species; matrix assisted laser desorption ionization time of flight mass spectrometry; microbial morphology; Mucor; Nectria; nonhuman; nucleotide sequence; Paecilomyces lilacinus; Penicillium; phylogeny; population abundance; priority journal; sponge (Porifera); taxonomic identification; Trichoderma; unindexed sequence; Xylariales; Zygomycetes; Animals; Ascomycota; Brazil; Culture Media; DNA, Fungal; Mitosporic Fungi; Mycological Typing Techniques; Phylogeny; Porifera; Ribotyping; Sequence Analysis, DNA; Dragmacidon; Fungi; Zygomycota